Observations on Red Palm Weevel Rhynchophorus ferrugineus in Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
Authors summarize available data on the biology of the Red Palm Weevel, reporting new information collected during a research carried out in Sicily, where this beetle has heavily damaged many historical gardens. They also record the first finding of the autochtonous parasitoid Billaea maritima (Schiner, 1862) (Diptera Tachinidae), hiterto known as antagonist of Cetoniinae.
Keywords: Rhynchophorus ferrugineus; Phoenix canariensis; damage; natural antagonists; Billaea maritima